(untitled) (Al-Academy, 2023)
The formal investigation of the interior spaces of the residential bedrooms for children with autism is one of the basic tasks that should be known by the interior designer. Achieving an atmosphere compatible with his health condition, which contributes to generating a sense of spatial intimacy through the design dimension provided by the interior designer and his tireless endeavor to meet the needs of the child in an internal environment that achieves the functional dimension and spiritual approaches that enhance the child’s sense of spatial belonging and contribute to improving his mood and this positively reflects on his behavior and social integration. The current research has reached the most important design criteria that must be available for the design of the interior spaces for autistic children represented by (the bedroom), which will be the first of its kind at the level of the interior design of residential spaces in Iraq.